Motivasi Belajar Mahasiswa Pada Pembelajaran Daring Selama Pandemik Covid-19 - Yani Fitriyani; Irfan Fauzi; Mia Zultrianti Sari (Universitas Pendidikan Mandalika (UNDIKMA), 2020)
This study aims to explain in detail how the objective motivational conditions experienced by students in online learning during the Covid-19 pandemic. This study used a quantitative approach with a survey method. The study was conducted at Universitas Kuningan involving 80 sixth semester students in the Elementary School Teacher Education study program. Data collection techniques used in this study were survey technique with a Likert scale. Survey was made through google form so that it was easily accessible by students. The data analysis technique used in this study was calculating the percentage of data from each indicator, interpreting the data presentation score andthen analyzing each indicator in depth. The results of this study indicated that the learning motivation of sixth semester students of the elementary school teacher education program at Universitas Kuningan was very good, in which the percentage score of motivation reached 80.27%. This study is expected to be an evaluation of various parties in organizing online learning in higher education, especially those involving motivation in it. This research is also expected to be a study material for other researchers in analyzing and developing student learning motivation in online learning during emergencies in higher education.